Mechanical properties of compacted graphite cast iron with different microstructures - Gregorutti, Ricardo Walter (2014)
Tensile strength, fracture toughness and impact properties were evaluated in compacted graphite (CG) cast iron with ferritic, pearlitic and ausferritic microstructures. Ultimate tensile strengths for the ferritic and pearlitic samples were 337 and 632 MPa respectively. The austempered samples showed a significant increment in the strength and recording values between 675 and 943 MPa. The fracture toughness test revealed that the stress–intensity factor KIC was 34.0 MPa m1/2 for the ferritic CG iron, 39.7 MPa m1/2 for the pearlitic and between 51.0 and 58.0 MPa m1/2 for the austempered irons. On the other hand, CG iron with ferritic matrix exhibited the best impact properties with absorbed energy of 33.3 J. The absorbed energy of the pearlitic CG iron was the lowest, 14.3 J, while the austempered samples showed values between 17.2 and 28.4 J. Complementing these results, the critical crack size was also analysed.